PENGARUH PENGGUNAAN MODEL PEMBELAJARAN MEANS ENDS ANALYSIS (MEA) TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA SISWA KELAS X SMA NEGERI 3 METRO - Yustika Kholida Rosdiana; HRA Mulyani; Agus Sujarwanta (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
This research is motivated by the low critical thinking skills of tenth-grade students at SMA Negeri 3 Metro, which is evident from their lack of active participation and difficulties in understanding biological technology innovation concepts. The study's objectives are to determine the influence of the Means Ends Analysis (MEA) learning model on students' critical thinking skills, and to find out which MEA model practicum-based or video-based is better at improving these skills. This experimental study used a Post-test Only Control Design. Two classes were randomly selected as the experimental group (practicum-based MEA) and the control group (video-based MEA). Critical thinking skills data were collected through a post-test and analyzed using normality, homogeneity, and an Independent Sample t-test. The results show that the MEA learning model significantly influenced students' critical thinking skills. The practicum group achieved an average score of 82.11, while the video group scored 77.71. This indicates that practicum-based MEA resulted in better critical thinking skills, although the difference was not drastic. The stages of MEA are effective in training students to explain, analyze, and conclude. Practicum activities encouraged active exploration and logical thinking, confirming that practicum-based MEA is an effective strategy for improving critical thinking in biology”.